Determination Reference of Concentration (RfC) Xylen Exposure Based on Xylen NOAEL in White Rats and Workers’ Body Weight and Height in Surabaya Car Painting Area, Indonesia (Indian Journal of Forensic Medicine & Toxicology, 2020)
This study aims to calculate the value of RfC from xylen exposure around the car painting area of Surabaya,Indonesia. This is an observational cross-sectional study with quantitative data analysis methods conductedmanually. The population in this study was groups of car painting workers and groups of car repairer on JalanPengenal Kota Surabaya. The sampling technique was proportionate stratified random sampling to take 51people. The measurement of xylen concentration around the car painting area was 635.98 mg/m3 (146.47ppm). This value is above the threshold value according to Minister of Manpower and TransmigrationRegulation Number 13 of 2011 and Minister of Manpower Regulation Number. 5 of 2018 is 434 mg/m3 (100ppm). RfC of car painting workers with NOAEL 50 mg/kg was 7.76 mg/kg.
Keywords: Xylen, RfC, car painting worker